2019
DOI: 10.1016/j.heliyon.2019.e01543
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using terrestrial fern (Gleichenia Pectinata (Willd.) C. Presl.): characterization and antimicrobial studies

Abstract: Novel silver nanoparticles from Gleichenia Pectinata (Willd.) C. Presl. was synthesized. A combination of spectroscopic and microscopic techniques were utilized to characterize the newly synthesized Gleichenia Pectinata Silver Nanoparticles (GPAgNPs) vis-a-vis UV-Vis Spectroscopy, Fourier Transform Infra-Red (FTIR) Spectroscopy, Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy Dispersive X-ray Spectroscopy (EDX) and X-Ray Diffraction (XRD) Analyses. Significant absorption was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(92 citation statements)
references
References 39 publications
18
47
0
1
Order By: Relevance
“…In the same regard, the weight percentage of Cu, Zn, O, C, and Na in the composite CuO/ZnO 20/80 was found to be 7.4%, 20.5%, 31.7%, 13.3%, and 27.1%, respectively, whereas it was 58.4%, 18.7%, 6.4%, 6.4%, and 10.1% , respectively, for the CuO/ZnO 80/20 composite. The presence of distinct peaks of C and Na may be attributed to the hydrolysis of the capping fungal metabolites containing proteins, sugars, amino groups, and carbohydrates by X-ray emissions [ 42 , 62 , 63 ]. The obtained data are in good agreement with that of Mohammadi-Aloucheh et al [ 42 ], where it was reported that the weight percentage of Zn, Cu, O, and C in a composite of ZnO/CuO (5%) synthesized using a leaf extract of Mentha longifolia was 72.1%, 4.1%, 21.4%, and 2.4%, respectively, and for the composite ZnO/CuO (10%), it was 73.2%, 4.3%, 19.2%, and 2.3% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the same regard, the weight percentage of Cu, Zn, O, C, and Na in the composite CuO/ZnO 20/80 was found to be 7.4%, 20.5%, 31.7%, 13.3%, and 27.1%, respectively, whereas it was 58.4%, 18.7%, 6.4%, 6.4%, and 10.1% , respectively, for the CuO/ZnO 80/20 composite. The presence of distinct peaks of C and Na may be attributed to the hydrolysis of the capping fungal metabolites containing proteins, sugars, amino groups, and carbohydrates by X-ray emissions [ 42 , 62 , 63 ]. The obtained data are in good agreement with that of Mohammadi-Aloucheh et al [ 42 ], where it was reported that the weight percentage of Zn, Cu, O, and C in a composite of ZnO/CuO (5%) synthesized using a leaf extract of Mentha longifolia was 72.1%, 4.1%, 21.4%, and 2.4%, respectively, and for the composite ZnO/CuO (10%), it was 73.2%, 4.3%, 19.2%, and 2.3% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this spectrum, a sharp absorption signal peak at 3433 cm −1 is related to the N–H bond of amine groups of green-synthesized Ag NPs and provides stabilization of Ag NPs. Hence, the occurrence of N–H group-specific proteins and enzymes correspond to the reduction of AgNO 3 to Ag [ 32 ]. A comparative study of the FTIR spectrum ofthe control shows the most important signal peaks of ~3433, 1632, and 1384 cm −1 , illustrating the N–H group’s presence on the surface of Ag NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly described mechanisms begin with silver ion release [ 31 ], followed by ROS generation [ 13 , 32 ] and cell membrane damage, but many ambiguous findings have been reported. Generally, the metal form of silver (Ag) nanocrystallites represents an optical peak at 3KeV because of their surface plasmon resonance [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SPR is due to the free electron arising from the conduction and valence bands lying close to each other in metal nanoparticles. It is as a result of the collective oscillation of free electron of silver nanoparticles in resonance with the light wave in silver nanoparticle synthesis (Dada et al., 2018a, b; Femi-Adepoju et al., 2019). Stable SPR peak was observed at 450 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%